2020
DOI: 10.1111/ijpo.12611
|View full text |Cite
|
Sign up to set email alerts
|

In utero exposure to gestational diabetes mellitus and cardiovascular risk factors in youth: A longitudinal analysis in the EPOCH cohort

Abstract: Summary Objective To examine associations of maternal gestational diabetes mellitus (GDM) with offspring cardiovascular biomarkers from late childhood through adolescence. Methods We used mixed effects linear regression models to examine associations of maternal GDM (n = 92 cases of 597) with average offspring levels of serum lipids (total cholesterol, high‐density lipoprotein [HDL], low‐density lipoprotein [LDL], and triglycerides) and systolic blood pressure (SBP) across two research visits spanning approxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…Only those predicted targets involved in ontologies of human diseases (obesity, hypertension, glucose intolerance, lipid metabolism disease, type 2 diabetes mellitus, heart septal defects and heart valve disease, heart disease, heart failure, venous insufficiency, and pulmonary embolism) reported by previous population-based cohort studies in children and young adults descending from GDM complicated pregnancies [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ] are presented below.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only those predicted targets involved in ontologies of human diseases (obesity, hypertension, glucose intolerance, lipid metabolism disease, type 2 diabetes mellitus, heart septal defects and heart valve disease, heart disease, heart failure, venous insufficiency, and pulmonary embolism) reported by previous population-based cohort studies in children and young adults descending from GDM complicated pregnancies [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ] are presented below.…”
Section: Methodsmentioning
confidence: 99%
“…Parallel, in 17-year-old offspring of mothers with GDM and higher mean BMI, systolic and diastolic BP values were observed when compared to no-recorded-GDM offspring [ 31 ]. Nevertheless, another recent study performed on youth (at the age of 10.6–16.9 years) demonstrated that maternal GDM was related to altered lipid profile and higher systolic blood pressure only in a sex-specific manner [ 32 ]. A higher total and LDL cholesterol were detected only in girls and a higher systolic blood pressure only in boys previously exposed in utero to GDM [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lifelong cardiovascular risk of children descending from pregnancy-related complications is based on the presence of overweight/obesity (increased body mass index and/or wider waist circumference) [1][2][3][4][5][6][7][8][9][10][11], higher systolic and/or diastolic blood pressures [1,2,[6][7][8][12][13][14][15][16][17][18][19][20][21][22], higher nocturnal systolic and diastolic blood pressures [16], altered lipid profiles [6,21], altered metabolite pattern [23], impaired glucose tolerance [3,[5][6][7]24], alteration in the systemic and the pulmonary circulation [25], altered cardiac geometry and function [26][27][28][29] and the acceleration of pubertal timing [30].…”
Section: Introductionmentioning
confidence: 99%
“…The rapid increase in pediatric obesity in recent decades has created a looming public health crisis. Mounting evidence implicates early life contributions to adiposity and cardiometabolic profiles later in life [ 1 , 2 , 3 , 4 ], and childhood obesity in particular has been associated with adult obesity, as well as many related comorbidities and diseases [ 5 ]. Risk for obesity is multifactorial and begins even before birth, with influence from factors such as genetics and in utero exposures [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%